Feedback cultures, histories and literacies: international postgraduate students' experiences. Issue 3 (11th April 2022) - Rovagnati, Veronica; Pitt, Edd; Winstone, Naomi
Abstract: Emerging research and examples from practice support the idea of feedback literacies as socio-material competencies. Such a conception highlights the contextual and social aspect of literacies but neglects their cultural aspect. Reality in higher education sees an increasingly international student body, particularly at postgraduate levels. International postgraduate students transitioning to new systems are likely to have developed diverse 'literacies' within their previous institutional cultures. Using narrative inquiry, this study collected in-depth stories of the assessment and feedback experiences of 10 international postgraduate taught students before and after transitioning to postgraduate education at a UK institution. The study gives accounts of the ways in which the students recognised, processed and utilised feedback. A combination of narrative and thematic analysis indicated a clear influence of culture- and context-shaped histories upon students' feedback literacies. Such diverse literacies do not mirror the UK 'norm' for feedback literacy and do not initially support students in making effective use of feedback in the new environment. These findings highlight that shifting our conceptualisation of feedback literacies from universal to context- and culture-specific is necessary, as is embedding diversity and intercultural interactions within the development of intercultural feedback literacies.